PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Tiket Garuda di PT.Totogasono Sekawan Samarinda Tahun 2016) - Idham Cholid (Jurnal Ekonomi dan Manajemen, 2018)
The aim to determine the effect of product Quality of Service on customer satisfaction at PT. Totogasono Sekawan Samarinda. Companies in running their business must apply Quality of Services, where Quality of service is one type of competitive advantage that can be owned by the company. Because of the suspected application of Service Quality is very influential on customer satisfaction of a company. This research was conducted by conducting research on Quality of service policy at PT. Totogasono Sekawan Samarinda. The method used is simple regression method and correlation coefficient and t test to see the influence and relationship of Quality of Service to customer satisfaction. The results showed that Quality Service has a strong relationship to customer satisfaction in PT. Totogasono Sekawan Samarinda. This is evidenced from the results obtained in testing the hypothesis where the value of t count = 6,251> from ttable = 2,021 at  = 0.05 or 5% and the correlation coefficient of 0,710 and the value of coefficient of determination = 86.3%, then the regression equation simple obtained is y = 0,600 sampai dengan 0,800 x. It means that every decrease of product differentiation as 1% in PT. Totogasono Sekawan Samarinda will increase consumer satisfaction equal to 0,800%. It was concluded that the key to success of PT. Totogasono Sekawan Samarinda in reaching and serving the market should apply the concept of product differentiation that can increase customer satisfaction and continue to be a successful company and can win the competition.